To start or to complete? - Challenges in implementing tuberculosis preventive therapy among people living with HIV: a mixed-methods study from Karnataka, India - Mahendra M. Reddy; Pruthu Thekkur; Nagesh Ramya; Prasanna B. T. Kamath; Suresh G. Shastri; Ravi B. N. Kumar; Palanivel Chinnakali; Abhay S. Nirgude; Chethana Rangaraju; Narasimhaiah Somashekar; Ajay M. V. Kumar (Taylor & Francis Group, 2020)
Background: Isoniazid preventive therapy (IPT) has been shown to reduce the risk of tuberculosis (TB) among people living with HIV (PLHIV). In 2017, India began a nationwide roll-out of IPT, but there is a lack of evidence on the implementation and the challenges. Objectives: Among PLHIV newly initiated on antiretroviral therapy (ART) from January 2017 to June 2018, to: (i) assess the proportion who started and completed IPT and (ii) explore reasons for non-initiation and non-completion from health-care providers' and patients' perspectives. Methods: An explanatory mixed-methods study was conducted in two selected districts of Karnataka, South India. A quantitative phase (cohort analysis of routinely collected program data) was followed by a qualitative phase involving thematic analysis of in-depth interviews with providers (n = 22) and patients (n = 8). Results: Of the 4020 included PLHIV, 3780 (94%) were eligible for IPT, of whom, 1496 (40%, 95% CI: 38%-41%) were initiated on IPT. Among those initiated, 423 (28.3%) were still on IPT at the time of analysis. Among 1073 patients with declared IPT outcomes 870 (81%, 95% CI: 79%-83%) had completed the six-month course of IPT. The main reason for IPT non-initiation and non-completion was frequent drug stock-outs. This required health-care providers to restrict IPT initiation in selected patient subgroups and earmark six-monthly courses for each patient to ensure that, once started, treatment was not interrupted. The other reasons for non-completion were adverse drug effects and loss to follow-up. Conclusion: The combined picture of 'low IPT initiation and high completion' seen in our study mirrors findings from other countries. Drug stock-out was the key challenge, which obliged health-care providers to prioritize 'IPT completion' over 'IPT initiation'. There is an urgent need to improve the procurement and supply chain management of isoniazid.